GLUT1-mediated glucose import in B cells is critical for anaplerotic balance and humoral immunity - Bierling, Theresa; Gumann, Amelie; Ottmann, Shannon; Schulz, Sebastian; Weckwerth, Leonie; Thomas, Jana; Geßner, Arne; Wichert, Magdalena; Kuwert, Frederic; Rost, Franziska; Hauke, Manuela; Freudenreich, Tatjana; et al. (Cell Reports, 2024)
Glucose uptake increases during B cell activation and antibody-secreting cell (ASC) differentiation, but conflicting findings prevent a clear metabolic profile at different stages of B cell activation. Deletion of the glucose transporter type 1 (GLUT1) gene in mature B cells (GLUT1-cKO) results in normal B cell development, but it reduces germinal center B cells and ASCs. GLUT1-cKO mice show decreased antigen-specific antibody titers after vaccination. In vitro, GLUT1-deficient B cells show impaired activation, whereas established plasmablasts abolish glycolysis, relying on mitochondrial activity and fatty acids. Transcriptomics and metabolomics reveal an altered anaplerotic balance in GLUT1-deficient ASCs. Despite attempts to compensate for glucose deprivation by increasing mitochondrial mass and gene expression associated with glycolysis, the tricarboxylic acid cycle, and hexosamine synthesis, GLUT1-deficient ASCs lack the metabolites for energy production and mitochondrial respiration, limiting protein synthesis. We identify GLUT1 as a critical metabolic player defining the germinal center response and humoral immunity.
CRIS-Team Scopus Importer:2024-02-23
Keywords: adaptive immune response; antibody-secreting cell; CP: Immunology; CP: Metabolism; glucose transporter type 1; GLUT1; glycolysis; metabolism; mitochondrial respiration; plasma cell; plasmablast